Application of Laser-Speckle Correlation Method for Blood Coagulation Estimation; Progress in Electromagnetics Research Symposium (PIERS-Toyama) - Li Lin; Sytnik Yu. D. Yuliya Dmitrievna; Pekker Ja. S. Jakob Semenowitsch; Gubarev F. A. Fedor Aleksandrovich (2018, 2018)
Title screen